EFFECTS OF ORGANIC FERTILIZERS AND WHEAT VARIETIES ON INFESTATION BY, CORN LEAF APHID, RHOPALOSIPHUM MAIDIS AND WHEAT THRIPS, HAPLOTHRIPS TRITICI AND THEIR PREDATORS - K. Khidr, S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A field trial has been conducted at the fields of Agriculture College/ Salahaddin University- Erbil in order to evaluate the addition of some organic fertilizers to some wheat varieties and their susceptibility to attack by both corn leaf aphid, Rhopalosiphum maidis and wheat thrips, Haplothrips tritici with their predators. Three types of organic fertilizers (livestock manure, poultry manure + plant compost & plant compost) in a rate of (10 m3/ ha) and synthetic fertilizer (NPK) at (0.1 m3/ha) were applied into the soil. There were significant effects of organic farming on decreasing the population density of both R. maidis and H. tritici in comparison with inorganic practices which recorded highest numbers (7.18 aphid/ tiller) and (2.84 thrips/spike) respectively, the Smito variety was more susceptible to attack by R. maidis  than Rzgari variety, while more resistant to H. tritici in comparison with Rzgari variety. In addition, more predators, Coccinella septumpunctata and Syrphus corolla were observed in organic compost than in chemical fertilizer treatments and controls. The field trial indicated that organic treatments (especially livestock manure and poultry manure + plant compost) were effective as synthetic fertilizer and therefore similar biological and grain yields were obtained when using various fertilizer types that differ from untreated control which had lower agronomic parameters